Depresión en tiempos del COVID 19 en docentes de nivel primaria de la Institución Inicial Primaria Secundaria de Menores N° 60756 Claverito, Iquitos 2021 - Ramirez Ochavano, Angela Luz (2022)
The general objective of the research was to describe the level of depression in times of COVID-19 in primary-level teachers of the Initial Primary Secondary Institution for minors No. 60756 Claverito located in Iquitos in 2021. The type of descriptive research, with a cross-sectional, univariate and field design. The study population was 26 directors and teachers of the educational institution, who were also part of the sample. To obtain the data referring to the research, the survey was used as a technique and a questionnaire validated by expert judgment. The conclusion is reached that the level of depression in times of covid 19 in primary level teachers of the Initial Primary Secondary Institution for minors N ° 60756 Claverito, is high in 11.5%, average level in 80.8% and only in 7.7% of them low level, which indicates that it is necessary to strengthen teachers with improvement actions that allow reducing the effects of this disease.